SCIENCE AND RELIGIONS IN AMERICA a new look. - Cootsona, Gregory S. ([S.l.] : ROUTLEDGE, 2023)
What is religion? What is science? How do they interact with each other? Science and Religions in America: A New Look offers a cutting-edge overview of the diverse range of religious traditions and their complex and fascinating interaction with science. Pluralistic in scope, the book is different from traditional Christian and/or monotheistic approaches to studying the rich interplay of religion and science in multi-religious American culture. Featuring interviews with specialists in the field, Greg Cootsona draws on their insights to provide a comprehensive, accessible, and engaging introduction to the challenging interrelationship of religion and science. Each chapter focuses on a different religion within the United States, covering Buddhism, Christianity, Nature Religions, Islam, Judaism, Hinduism, and the Spiritual but Not Religious (SBNR). Global religious traditions and their inextricable relationship with science and technology are examined in an accessible and interactive format. With "lightning round Q&As," contributions from leading thinkers, and suggestions for further reading, this book primes undergraduate students for studying the interchange of science and religions (in the plural) and is an exciting new resource for those interested in these topics in contemporary America.
Keywords: Religion and science -- United States; RELIGION / Religion & Science; RELIGION / Comparative Religion